Conceptual Framework of Innovation Excellence Model for Higher Education Institutions - Mohd Rashid, Ab Hamid; Mokhtar, Abdullah; Zainol, Mustafa; Nur Balqishanis, Zainal Abidin; Hanafiah, Ahmad (Elsevier, 2015)
This article presents the conceptual framework of Innovation Excellence Framework for education especially higher education institutions (HEI). Several factors were identified from previous studies through literature study and empirical findings. The original version of Total Performance Excellence Model was used as the main skeleton and its extended model called Value-Based Total Performance Excellence Model (VBPTEM) as the basis for this framework. Innovation Excellence Framework provides the staff at all level in the university to embark on innovation capabilities endeavor towards improved university performance. Several predictors of performance in the earlier version of TPEM and VBTPEM model have been regrouped into another viewpoint of university excellence in terms of innovation. Originally, there were 11 factors in the performance excellence model i.e. leadership, culture, objectives and strategy, resources management, change management, innovation values, best practices, employee-focused, stakeholder-focused, productivity-focused and total performance. Eventually, this article blends the available criteria into several sub-categories to give new insights towards empowering the innovation excellence at the HEI. The proposed conceptual framework is also presented.